The Role of Artificial Intelligence Applications in Improving Financial Productivity of Private Placements Firms - Ghassan Abdulkareem, Mohammed; Abdulaali Duair Albohabeeb, Waael; Khayoon Abbas, Hasan; Abdullah Abbas, Yasir (South Asian Journal of Social Sciences and Humanities, 2025)
This research aims to examine the role of artificial intelligence applications (AI) in enhancing and improving the financial productivity of private equity firms. The study tested 118 private placement firms in Malaysia from 2019 to 2024, by using secondary data and annual reports. The research results indicate that AI is positively associated with improving the financial productivity of private placement firms. AI has become an effective instrument in managing and enhancing operational processes; its advanced analytical capabilities, automation of prediction of market trends, repetitive tasks, and decision-making depend on large amounts of data. A range of AI applications were analyzed, and the AI has become a critical factor in enhancing financial productivity in companies and institutions, with multiple impacts spanning operational, analytical, and strategic aspects.